Reading in the Digital Age: Using Electronic Books as a Teaching Tool for Beginning Readers / La lecture à l'ère numérique: l'utilisation de livres électroniques comme outil d'enseignement pour les lecteurs débutants - Katia Ciampa (The Canadian Network for Innovation in Education (CNIE), 2012)
This study stemmed from a concern of the perceived decline in students' reading motivation after the early years of schooling. This research investigated the effectiveness of online eBooks on eight grade 1 students' reading motivation. Eight students were given ten 25-minute sessions with the software programs over 15 weeks. Qualitative data were collected from students, teachers, and parents through questionnaires, interviews, observations and field notes. The results suggest the promise of online reading software programs in supporting early readers with reading, motivation, and/or behavioural difficulties. La motivation des lecteurs débutants et les textes qu'ils choisissent de lire ont un impact sur leur succès en littératie et sur leur volonté de prendre part à des activités de lecture au cours des années du primaire. Cette étude s'est penchée sur les expériences de lecture de livres électroniques de huit élèves de première année. Huit élèves ont reçu 10 séances de 25 minutes avec les logiciels sur une période de 15 semaines. Des données qualitatives ont été recueillies auprès des élèves, des enseignants et des parents par l'entremise de questionnaires, d'entrevues, d'observations et de notes. Les résultats suggèrent que les livres électroniques sont prometteurs pour stimuler la motivation des lecteurs débutants.